Sharia Governance in Islamic Financial Technology: A Systematic Literature Review and Future Research Agenda - Taufiq Ramadhan; Wildan Sifaudin; Husnul Hotimah; MUhammad Iman Kurniawan; Arga Aditya Firmansyah (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2026)
Sharia governance has long been treated as an internal compliance apparatus built around the Sharia supervisory board, yet the digitalisation of Islamic finance has moved the object of governance beyond the boundaries of the conventional Islamic bank. This study reviews how the literature has framed Sharia governance in the context of Islamic financial technology and identifies the conceptual, contextual and methodological gaps that remain. Following the PRISMA protocol, 319 records were retrieved from Scopus and screened against publication window, journal quartile, duplication and abstract availability, yielding 86 studies published between 2015 and 2026. The corpus was coded thematically and organised through the Context, Intervention, Mechanism and Outcome logic. The results show a field geographically concentrated in Indonesia, Malaysia and the Gulf and Middle East and North Africa region, epistemologically dominated by agency theory, and methodologically weighted towards panel regression on secondary disclosure data, with quantitative designs accounting for 48.8 per cent of the classifiable corpus. Three findings stand out. The intervention repertoire remains structural, centred on board composition and disclosure, while technology enabled instruments are asserted rather than tested. The mechanisms documented in qualitative work, including fatwa repositioning, impression management and identity drift, indicate that compliance is negotiated rather than enforced, which the dominant quantitative apparatus cannot capture. Reported outcomes stop at financial performance, risk mitigation and disclosure quality, leaving maqasid oriented outcomes unmeasured. The study proposes a research agenda organised around hybrid governance design, algorithmic accountability and cross jurisdictional harmonisation.